Comparison of Methods to Reduce Grid Orientation Effect in Miscible Flood Simulation - Wan Ahmad Fuad Ali bin Wan Abd Ghafar, Wan Ahmad Fuad Ali (Universiti Teknologi Petronas, 2008)
Numerical dispersion is an artefact of current numerical analysis techniques that can cause severe distortions in simulations of processes in which relatively rapid saturation changes occur. Grid Orientation Effect (GOE) is a phenomenon in simulation caused by numerical dispersion, in which calculated performance is influenced by the orientation of the grid relative to the locations of injection and production wells. Pressures as well as saturations are distorted by grid orientation. This effect can cause serious problems in simulation of steam flooding or miscible-gas displacements. Therefore it is the objectives of this project to investigate the seriousness of this problem and the means in reducing the effect, using a numerical simulation. Carbon dioxide (CO2) miscible flooding process is being simulated on a homogeneous conceptual model, utilizing both parallel and diagonal grid configurations. Three methods of reducing GOE were studies; namely the two point upstream weightage method, nine-point scheme and increment of grid block (refining grid). Results were analysed and compared to evaluate the effectiveness of each method used. Results showed that the nine-point scheme gives the highest incremental recovery. However, in overall, combination of the three methods in parallel orientation yields the highest increment (9.15%). The average result for comparing the highest in parallel orientation and the lowest in diagonal orientation is 6.906%. Since the result is around 7%, it can be concluded that the results are converging.